Negotiating insanity in the southeast of Ireland, 1820-1900 - Cox, Catherine, 1970- (Manchester University Press ; Distributed in the United States exclusively by Palgrave Macmillan, 2012)
This text explores local medical, lay and legal negotiations with the asylum system in 19th-century Ireland. It deepens our understanding of protagonists' attitudes towards the mentally ill and institutional provision for the care and containment of people diagnosed as insane.